Patient perception of medial patellofemoral ligament reconstruction on Instagram. Issue 4 (9th June 2022) - Rizkalla, James M.; Holderread, Brendan; Botros, David; Orozco, Erin; Botros, Andro; Botros, Anthony; Wilson, Philip; Ellis, Henry
Abstract: To date, there is limited social media evaluation of patients after medial patellofemoral ligament (MPFL) reconstruction and analysis of their perceived surgical outcome. The purpose of this study was to examine patient perceived outcomes after MPFL reconstruction via social media analysis on Instagram. A total of 486 posts containing "#MPFL" were included in the assessment. The tone of the post was examined in relation to demographic variables and the content of the post. When comparing posts containing positive vs. negative tone, those referencing rehabilitation ( P < 0.0001) and activities of daily living (ADLs) ( P = 0.0002) were more likely to be positive. Posts referencing surgical incision or scar ( P = 0.02) or postoperative instability/dislocation ( P < 0.0001) were more likely to have a negative tone. Multivariable logistic regression identified references to incision/scar (odds ratio [OR]: 0.446, P = 0.0264) and instability/dislocation (OR: 0.071, P < 0.0001) as strong negative predictors of positive tone. However, referencing rehabilitation (OR: 2.464, P = 0.0091) or ADLs (OR: 2.251, P = 0.0187) substantially increased the likelihood of a positive post tone. In conclusion, positive tone was associated with improved rehabilitation and ability to perform ADLs postoperatively. In contrast, negative tone was associated with dissatisfaction with the scar/incision, as well as postoperative patellar instability.